2014
DOI: 10.1111/ppa.12210
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution melting analysis for rapid detection and characterization of Botrytis cinerea phenotypes resistant to fenhexamid and boscalid

Abstract: A novel, high-resolution melting (HRM) analysis was developed to detect single nucleotide polymorphisms (SNPs) associated with resistance to fenhexamid (hydroxyanilides) and boscalid (succinate dehydrogenase inhibitors) in Botrytis cinerea isolates. Thirty-six single-spore isolates arising from 13 phenotypes were selected and tested for fungicide sensitivity. Germ tube elongation assays showed two distinct sensitivity levels for each fungicide. Sequencing revealed that resistance to fenhexamid was due to a nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 30 publications
0
32
0
Order By: Relevance
“…In our lab we have recently developed a rapid (requiring less than 2 h) and simple method for the screening of fungicide resistance. The method is also able to detect the most common SNPs associated with resistance of B. cinerea representative isolates to these fungicides (Chatzidimopoulos et al 2014). In vitro bioassays and direct sequencing showed a 100 % correlation with detection of resistance.…”
Section: Applications Of Hrm Analysis In Plant Fungal Diagnosticsmentioning
confidence: 97%
See 1 more Smart Citation
“…In our lab we have recently developed a rapid (requiring less than 2 h) and simple method for the screening of fungicide resistance. The method is also able to detect the most common SNPs associated with resistance of B. cinerea representative isolates to these fungicides (Chatzidimopoulos et al 2014). In vitro bioassays and direct sequencing showed a 100 % correlation with detection of resistance.…”
Section: Applications Of Hrm Analysis In Plant Fungal Diagnosticsmentioning
confidence: 97%
“…Additionally, Ganopoulos et al (2013) suggested that HRM curves could be imported in the form of numerical data in analysis programs, thus permitting the comparison of the results from different laboratories, but such a process should be treated with caution, as the results may be influenced by several factors such as DNA quantity and quality, the chromophore and the instrument used. Finally, a shorter length of amplicon is desirable not only to overcome possibilities that natural polymorphisms may be present in the target amplicons (Chatzidimopoulos et al 2014), but also to form more distinguishable clusters as Tm can change greatly .…”
Section: Technical Considerationsmentioning
confidence: 99%
“…However, to smoothly operate the HRM analysis, all DNA samples should be prepared by a single extraction protocol. If differences exist in the concentrations of the template DNA, PCR amplification will result in different yields of PCR product, which will further influence the melting analysis (Chatzidimopoulos et al ., ). In the present assay, it was observed that the use of the HRM kit reduced the variation in the melting curves' formation.…”
Section: Resultsmentioning
confidence: 97%
“…In addition, the method is time consuming, and the result is easily influenced by culture conditions and the quality of the chemicals; thorough validation is important. Along with elucidation of the resistance mechanisms of some fungicides, molecular techniques are increasingly widely used in rapid detection of fungicide resistance, such as the amplification refractory mutation system (ARMS), PCR‐RFLP, real‐time PCR and high‐resolution melting analysis (HRM) . Recently, a recessive nuclear gene PvCesA3 controlling the resistance of P. viticola to CAA fungicide was reported .…”
Section: Discussionmentioning
confidence: 99%